2008
DOI: 10.1158/0008-5472.can-08-1708
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-Associated Antigen 9 Is Associated With Tumor Growth, Migration, and Invasion in Renal Cell Carcinoma

Abstract: Renal cell carcinoma (RCC) represents one of the most resistant tumors to radiation and chemotherapy. Current therapies for RCC patients are inefficient due to the lack of diagnostic and therapeutic markers. Our recent studies have suggested an association of sperm-associated antigen 9 (SPAG9) with ovarian carcinomas. In the present study, we investigated the clinical relevance of SPAG9 in RCC patients. RT-PCR analysis showed expression of SPAG9 transcript in RCC tissues and RCC cell lines. In situ RNA hybridi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
96
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 37 publications
5
96
0
Order By: Relevance
“…SPAG9 gene is located at the chromosome 17q21, which is a region involved in amplification and expression of cancer-related genes (Jagadish et al, 2005b). Although it was originally thought to be expressed exclusively in testis, ongoing research revealed SPAG9 expression in numerous tumors originating from various sites and organs such as brain, thyroid, breast, lung, kidney, colon, ovary, cervix, and endometrium (Garg et al, 2008, Garg et al, 2009a, Garg et al, 2009b, Kanojia et al, 2009, Kanojia et al, 2011, Yu et al, 2012, Wang et al, 2013, Yi et al, 2013. In a study by Garg et al (2007), SPAG9 expression and host immune responses were investigated in epithelial ovarian cancer (EOC) specimens and human ovarian cancer cell lines (Garg et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…SPAG9 gene is located at the chromosome 17q21, which is a region involved in amplification and expression of cancer-related genes (Jagadish et al, 2005b). Although it was originally thought to be expressed exclusively in testis, ongoing research revealed SPAG9 expression in numerous tumors originating from various sites and organs such as brain, thyroid, breast, lung, kidney, colon, ovary, cervix, and endometrium (Garg et al, 2008, Garg et al, 2009a, Garg et al, 2009b, Kanojia et al, 2009, Kanojia et al, 2011, Yu et al, 2012, Wang et al, 2013, Yi et al, 2013. In a study by Garg et al (2007), SPAG9 expression and host immune responses were investigated in epithelial ovarian cancer (EOC) specimens and human ovarian cancer cell lines (Garg et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…16 The JNK signaling interaction is well known to play an important regulatory role in cell proliferation, differentiation, apoptosis, cellular transformation, and tumor cell growth, and may be equally important for the outcome of SPAG9 expression in the cervix. 16,27,28 To our knowledge, the mechanism underlying the association between SPAG9 and carcinogenesis is still unclear. Perhaps the overexpression of SPAG9 changes the stability or kinetics of MAPK signaling pathways, leading to facilitation of cell invasion and migration; this warrants further studies.…”
Section: Discussionmentioning
confidence: 99%
“…COLO 205 or HCT 116 cells (1 ϫ 10 5 ) were plated in 6-well plates, allowed to attach, and were transiently transfected using Lipofectamine reagent (Invitrogen, Life Technologies, Carlsbad, CA) according to the manufacturer's instructions and as described previously. 13 …”
Section: Cell Lines and Transient Transfectionmentioning
confidence: 99%
“…6,12 Cancer-specific alternatively spliced mRNAs and protein isoforms may be used as cancer biomarkers. Our recent study demonstrated SPAG9 expression and its association with clinicopathological characteristics of tumors in renal cell carcinoma, 13 epithelial ovarian cancer, 14 breast cancer, 15 cervical carcinoma, 16 and thyroid cancer. 17 These findings suggest that SPAG9 may have a role in early spread of disease.…”
mentioning
confidence: 92%